Polycaprolactone/chitosan blends: Simulation and experimental design. (15th January 2016) - Zhang, Hongping; Luo, Xuegang; Lin, Xiaoyan; Lu, Xiong; Zhou, Yanfang; Tang, Youhong
Abstract: The morphologies and properties of polycaprolactone (PCL)/chitosan (CS) blends were studied by experiment and dissipative particle dynamics (DPD) simulation. The simulation predicted the morphologies and dispersion of PCL/CS blends with different PCL/CS ratios. Experiments were performed for characterising morphology, thermal and mechanical properties. Both experimental and DPD simulation results indicated that the PCL/CS blend with weight ratio 90/10 possessed homogeneous morphology with excellent ductility. The study indicated that the combination of experiments and the computer simulation can be an effective way of designing and developing the polymer blends with the tailored properties. Graphical abstract: DPD simulation helps to design the PCL/CS blends with the better mechanical properties. Highlights: The morphology and miscibility of PCL/CS blends were investigated by DPD simulation. The morphology and mechanical properties were determined experimentally. The PCL/CS (90/10) blend was found to be the most promising. Combining experiments and simulation was found to be an effective way of designing blends.